Different Methods in Volleyball Training Application Methodology (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article summarizes the methods, tools, and theoretical knowledge of their content for conducting technical, physical, and psychological training for volleyball players, and for use in preparing 15-17-year-old volleyball players for competitions. intended. It can be used by masters of physical culture and physical education teachers of secondary schools, coaches of primary training groups of volleyball players of children's and youth schools, and fans of this sport.